2002
DOI: 10.1021/np0105073
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Stilbenoids from Stemona collinsae

Abstract: Fifteen new stilbenoids including 11 phenylbenzofurans, the stemofurans A-K (1-11), and four dihydrostilbenes, the stilbostemins A (15), C (17), E (19), and F (20), were isolated and identified from a methanolic extract of Stemona collinsae roots together with five known derivatives, the stilbenes pinosylvin (13) and 4'-methylpinosylvin (14), the dihydrostilbenes, stilbostemins B (16) and D (18), and the dihydrophenanthrene racemosol (12) as well as (+)-sesamin, coniferyl alcohol, and stigmasterol. Bioautograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
97
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(107 citation statements)
references
References 21 publications
10
97
0
Order By: Relevance
“…Due to their effective pharmacological activities, these compounds have been extensively studied. [1][2][3][4][5] A literature survey revealed that most 2-phenylbenzofurans with hydroxy and methoxy groups demonstrated multi-bioactivities, including antitumor, 6,7) anti-microbial, [8][9][10] antivirus, 11) adenosine A 1 receptor antagonists 12,13) and immunosuppressant properties. 14) In recent years, it is found that 2-phenylbenzofurans have significant binding affinity and selectivity on estrogen receptor (ER)β.…”
mentioning
confidence: 99%
“…Due to their effective pharmacological activities, these compounds have been extensively studied. [1][2][3][4][5] A literature survey revealed that most 2-phenylbenzofurans with hydroxy and methoxy groups demonstrated multi-bioactivities, including antitumor, 6,7) anti-microbial, [8][9][10] antivirus, 11) adenosine A 1 receptor antagonists 12,13) and immunosuppressant properties. 14) In recent years, it is found that 2-phenylbenzofurans have significant binding affinity and selectivity on estrogen receptor (ER)β.…”
mentioning
confidence: 99%
“…Deprotection of the two MOM ethers with concentrated HCl in methanol afforded compound 20 (90%), known as stilbostemin B. This compound was isolated from Stemona collinsae 20 and S. sessilifolia, 21 which have long been used in traditional Chinese and Vietnamese medicines for the treatment of inflammatory related diseases. "Baibu", the dried root tuber of Stemona sessilifolia, is listed in the Chinese Pharmacopoeia and used to relieve cough and kill insects and worms.…”
Section: Resultsmentioning
confidence: 99%
“…22 In Vietnamese medicine, S. collinsae has been used for cough relief and as an antiasthmatic. 23 Naturally occurring stilbostemin B (20) showed strong antifungal 24 and antibacterial 25 activities, along with inhibition of leukotriene formation.…”
Section: Resultsmentioning
confidence: 99%
“…Pinosylvin (1) is considered a stilbenoid found in nature and commonly located in leaves and heartwoods Data are represented as the mean ± SD (n =4) in mg/g of the MeOH extracts of samples ND: Not detected of Pinus species. Stilbenoids (Pinosylvin) showed the strong antifungal activity against Pyricularia grisea and Alternaria citri (Pacher et al 2002).…”
Section: Hplc Analysis Of Pinosylvin (1)mentioning
confidence: 99%